2016
DOI: 10.3390/ijms17040475
|View full text |Cite
|
Sign up to set email alerts
|

Combining miRNA and mRNA Expression Profiles in Wilms Tumor Subtypes

Abstract: Wilms tumor (WT) is the most common childhood renal cancer. Recent findings of mutations in microRNA (miRNA) processing proteins suggest a pivotal role of miRNAs in WT genesis. We performed miRNA expression profiling of 36 WTs of different subtypes and four normal kidney tissues using microarrays. Additionally, we determined the gene expression profile of 28 of these tumors to identify potentially correlated target genes and affected pathways. We identified 85 miRNAs and 2107 messenger RNAs (mRNA) differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 60 publications
1
36
1
1
Order By: Relevance
“…After identifying outliers (adjusted P -values < 0.01, see Methods), we have gotten 55 miRNAs and 1114 probes attributed to each mRNA, respectively. One should note that these numbers were much smaller than those identified by Luding et al [3]. Thus, since these are feasible, our methodology has more power to get limited number of critical miRNAs/mRNAs.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…After identifying outliers (adjusted P -values < 0.01, see Methods), we have gotten 55 miRNAs and 1114 probes attributed to each mRNA, respectively. One should note that these numbers were much smaller than those identified by Luding et al [3]. Thus, since these are feasible, our methodology has more power to get limited number of critical miRNAs/mRNAs.…”
Section: Resultsmentioning
confidence: 78%
“…It worked pretty well although it was not modified from samples to samples (from cohorts to cohorts) so as to get feasible results, but employed single common criterion to identify feasible miRNA-mRNA pairs. In this paper, the almost same strategy was applied to data set used by Luding et al [3], and it turned out to work well for these data sets; for example, top 15 down-regulated miRNAs in Wilms tumor compared with normal kidney shown in thier Table 1 were almost identified without optimizing almost anything (no FC threshold, no specified number of top ranked miRNAs, and adjusted Pvalues are used).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies with patient samples have used targeted exome sequencing to categorize additional mutations in WT. Apart from the genes that are involved in kidney development, a new category of mutations in the microRNA processing pathway (Wegert et al, 2015, Gadd et al, 2017, Ludwig et al, 2016 was identified.…”
Section: Introductionmentioning
confidence: 99%